Penerapan Naïve bayes untuk Analisis Faktor-Faktor Pemilihan STMIK AKAKOM sebagai Tempat Studi - Danny Kriestanto; Femi Dwi Astuti (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Students that are going to continue their study in University has a wide variety of choices. This study is going to find the what are the motives of the student to choose STMIK AKAKOM using Naive Bayes. Primary data were used based on certain judgments and were taken from active students with different backgrounds for the last 5 years. The questionnaire was filled out online.  Respondents will be validated to make sure it was truly active students of STMIK AKAKOM. This was a 5-point Likert scale closed questionnaire. The respondents were consists of 60% male and 40% female with from 18-22 years old students, with 64% of the whole respondents were from Information System Department. 62% of the respondents came from the Special Region of Yogyakarta and 40% of them were never taken out PTN entrance exam. The result of this study was based on the analysis of Naive Bayes: the first rank was because of the quality, the second rank was because of the promotion, and the last one because of the tuition fees